2010
DOI: 10.1007/s00540-009-0865-x
|View full text |Cite
|
Sign up to set email alerts
|

Possible indications of beta-blockers in the perioperative period other than prevention of cardiac ischemia

Abstract: According to the guidelines of the American College of Cardiology/American Heart Association 2006 for perioperative cardiovascular evaluation for non-cardiac surgery, beta-blocker therapy should be considered for high-risk individuals undergoing vascular surgery or high- and intermediate-risk patients undergoing non-cardiac surgery. This guideline might induce physicians to increasingly use beta-blockers in the hope of preventing perioperative cardiac complications. However, beta-blockers have potential benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 138 publications
0
13
0
1
Order By: Relevance
“…Besides, a peripheral anti-inflammatory action-related antinociception has also been proposed. [37] Another theory of anesthetic-sparing effects relates to the reduction in cardiac output and hepatic blood flow associated with esmolol influencing the distribution of pharmacokinetics, metabolism, and clearance of propofol or volatile anesthetic agents. [38] Despite the experimental and clinical data relating to a possible antinociceptive effect, the current evidence favoring an inherent analgesic property of esmolol is very weak.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, a peripheral anti-inflammatory action-related antinociception has also been proposed. [37] Another theory of anesthetic-sparing effects relates to the reduction in cardiac output and hepatic blood flow associated with esmolol influencing the distribution of pharmacokinetics, metabolism, and clearance of propofol or volatile anesthetic agents. [38] Despite the experimental and clinical data relating to a possible antinociceptive effect, the current evidence favoring an inherent analgesic property of esmolol is very weak.…”
Section: Discussionmentioning
confidence: 99%
“…[38] Despite the experimental and clinical data relating to a possible antinociceptive effect, the current evidence favoring an inherent analgesic property of esmolol is very weak. [373940]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Очевидно, что назначение БАБ в периоперационном периоде должно определяться наличием показаний к их применению независимо от предстоящей хи-рургической операции. Кроме того, в ряде случаев БАБ применяются в периоперационном периоде не толь-ко с целью снижения сердечно-сосудистого риска, а, например, для нейропротекции при травмах головного мозга или вводятся интратекально (эндолюмбально, под оболочки спинного мозга) для усиления антино-цицептивного (противоболевого) эффекта [32]. Од-нако, рекомендуемый временной интервал (опти-мально за месяц до операции) не всегда оправдан с точки зрения своевременности хирургического лече-ния, а титрование дозы до достижения целевых значений ЧСС нередко требует повторных врачебных консультаций.…”
Section: заключениеunclassified
“…It has been reported that the stress response and inflammatory response markedly increase postoperatively and last for 2-3 d (7). In addition, short-term perioperative propranolol or parecoxib administration has been clinically proven to be safer than chronic drug administration and has additional benefits, such as reduction of the dosage of anesthetic and analgesic agents and protection of patients from stroke and cardiac complications (31).…”
Section: The Journal Of Immunologymentioning
confidence: 99%